Variation Techniques in Four West African Lead Drumming Examples: A Comparative Study - Jeryl Johnston (Analytical Approaches to World Music)
Contrary to the mythologies of both oversimplification and esoterism so often mistakenly associated with African music, lead drummers of various West African musical traditions often organize their musical material using similar coherent, sophisticated, and measurable techniques. To begin to illustrate this, I compare studies of gahu and adowa by David Locke (1998) and Willie Anku (1992) to two transcriptions that I have prepared: “Miwua Agbo Mayi,” an example of agbadza, and “Esikesi,” a dùndún performance. I analyze the lead drum parts according to organizational techniques defined by Locke, Anku and Simha Arom (2004). Additionally, I provide basic background information about each genre, along with analyses of form for the two cases in which none have been provided before. I focus on these examples’ common techniques of organizing rhythmic variations: variation by amplification, timing displacement, filling or emptying of musical space, and segmentation.